Aplikasi Pelarut Eutektik K2CO3-Gliserol pada Ekstraksi Pigmen Antosianin dari Kulit Manggis (Garcinia mangostana Linn.) - Asni, Hazima; Manurung, Renita; Bonella, Dian (Jurnal Teknik Kimia USU, 2020)
Mangosteen peel (Garcinia mangostana Linn.) contains 593 ppm of anthocyanin. Anthocyanin pigment from mangosteen peel (Garcinia Mangostana Linn.) can be used as an alternative to synthetic dyes. Eutectic solvents are the latest development in extraction technology to extract anthocyanin from its source. The solvent used is pottasium carbonate-glycerol based eutectic solvent. The purpose of this study was to determine the effect of eutectic solvents on the extraction of anthocyanin pigments from mangosteen peel. This research consists of 2 treatment factors namely rmolar ratio of K2CO3: glycerol of 1: 5, 1: 6, and 1: 7 and material: solvent ratio of 1: 4, 1: 6 and 1: 8. Anthocyanin content and color intensity were analyzed using a Spectrophotometer UV-Vis.Â  Extraction using K2CO3 : glycerol eutectic solvent at a ratio of 1: 7 and the ratio of material: solvent 1: 8 produced the best treatment with extract yield of 46%; anthocyanin content of 263.976 mg/L, and color intensity value of 0.173.